2020
DOI: 10.2967/jnumed.120.242180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 68Ga-PSMA-11 PET on the Management of Recurrent Prostate Cancer in a Prospective Single-Arm Clinical Trial

Abstract: Prostate-specific membrane antigen (PSMA) ligand PET induces management changes in patients with prostate cancer. We aim to better characterize the impact of 68 Ga-PSMA-11 PET ( 68 Ga-PSMA PET) on management of recurrent prostate cancer in a large prospective cohort. Methods: We report management changes after 68 Ga-PSMA PET, a secondary endpoint of a prospective multicenter trial in men with biochemical recurrence of prostate cancer. Pre-PET (Q1), post-PET (Q2), and posttreatment (Q3) questionnaires were sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 22 publications
4
64
1
2
Order By: Relevance
“…Although the direction of management change is diverse, there is a detectable pattern [35]. Patients with undetectable disease using 68 Ga‐PSMA tracers were more often switched to no treatment, whereas patients with local recurrence were switched to local therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the direction of management change is diverse, there is a detectable pattern [35]. Patients with undetectable disease using 68 Ga‐PSMA tracers were more often switched to no treatment, whereas patients with local recurrence were switched to local therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional imaging techniques, including magnetic resonance imaging (MRI) and computed tomography (CT) (3), have limited sensitivity. Since 2012, the application of 68 Ga-prostate-specific membrane antigen (PSMA) positron emission tomography (PET)-CT has significantly improved detection rates in BCR patients (4)(5)(6)(7). Various studies showed that 68Ga-PSMA PET-CT detection efficiency is higher than conventional imaging approaches and choline PET (4,8).…”
Section: Introductionmentioning
confidence: 99%
“…If a patient's PSA starts to rise following a cycle of ADT and SBRT, we recommend repeat PET imaging when the patient's PSA rises to ≥1 ng/ml. At this PSA level, PSMA-PET has been shown to perform well in the detection (> 80%) of recurrent prostate cancer ( 67 ). While the performance of PET imaging improves with increasing PSA, this PSA cut off balances a relatively high rate of disease detection without allowing undue progression of disease that may sacrifice clinical outcomes ( 68 ).…”
Section: A Cycle-based Treatment Approachmentioning
confidence: 99%